Speech motor impairment in ALS is associated with multiregional cortical thinning beyond primary motor cortex - Zaninotto, Ana Luiza; Makary, Meena M.; Rowe, Hannah P.; Eshghi, Marziye; Tseng, Chieh-En (Jane); Chan, James; Zürcher, Nicole R.; Hooker, Jacob; Lewis, Austin; Keegan, Mackenzie; Gifford, Ryan F.; Green, Jordan R.; et al. (Frontiers in Neurology, 2024)
Cortical thinning is well-documented in individuals with amyotrophic lateral sclerosis (ALS), yet its association with speech deterioration remains understudied. This study characterizes anatomical changes in the brain within the context of speech impairment patterns in individuals with ALS, providing insight into the disease's multiregional spread and biology. To evaluate patterns of cortical thickness in speakers with ALS with and without functional speech changes compared to healthy controls (HCs) using whole-brain and region of interest (ROI) analyses. Forty individuals with ALS and 22 HCs underwent a T1-weighted 3-Tesla magnetic resonance imaging (MRI). Individuals with ALS were divided into two groups based on the preserved speech [ps-ALS] (n= 18) or deteriorated speech [ds-ALS] (n= 22) as measured by the ALSFRSF-R speech subscore (=4 or <4 points, respectively). Sixteen a priori-defined and automatically segmented cortical and subcortical brain ROIs were selected based on their previously documented roles in speech production. Two cortical thickness analyses were performed: (1) group-level whole-brain surface-based analyses and (2) group-level ROI analyses. A case study of 6 ALS individuals examined the cortical thickness, and their speech was characterized using quantitative and qualitative measures. Based on the group-level whole-brain surface-based analyses, the ds-ALS group demonstrated significant cortical thinning compared to HCs in the left primary motor and somatosensory cortices and the right inferior parietal lobe with its adjacent lateral occipital cortical regions. The ps-ALS group demonstrated no significant cortical thinning compared to HCs. Based on the group-level ROI analyses, the ds-ALS group demonstrated significant cortical thinning compared to HCs in bilateral middle motor cortices, right posterior dorsal premotor cortex, and left anterior cingulate cortex. The case study analysis revealed that ALS speakers with speech features characteristic of spastic dysarthria exhibited cortical thinning, while those with speech features characteristic of flaccid dysarthria did not. Individuals with ALS have anatomical changes involving multiregional neocortical areas beyond the primary motor cortex that may manifest as subjective (i.e., clinical judgment) and objective (i.e., speaking rate) changes in speech production. Further longitudinal work in ALS is needed to better understand the link between MRI cortical thickness changes and bulbar dysfunction.